2014
DOI: 10.3233/thc-140788
|View full text |Cite
|
Sign up to set email alerts
|

Use of three-dimensional computed tomography images in dental care of children and adolescents in Korea

Abstract: Advances in computed tomography (CT) technology -from traditional CT to cone beam (CB) CT -have benefitted both the dentists and their young patients. We therefore wanted to determine the prevalence of CBCT use in pediatric dentistry in Korea.Our first approach was to conduct an institutional survey to evaluate the use of CBCT for diagnosing and evaluating dental problems in pediatric patients. Our second approach was to review any articles published during 2002-2011 in the Journal of the Korean Academy of Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The use of CBCT in pediatric dentistry has been mentioned in the dental literature. A research from Korea demonstrated the most prevalent usage of CBCT among children and adolescents were for diagnosis and monitoring of the growth of cysts and other tumors, following by localization of impacted teeth, and supernumerary teeth [87].…”
Section: Emerging Trends In Oral Health Sciences and Dentistrymentioning
confidence: 99%
“…The use of CBCT in pediatric dentistry has been mentioned in the dental literature. A research from Korea demonstrated the most prevalent usage of CBCT among children and adolescents were for diagnosis and monitoring of the growth of cysts and other tumors, following by localization of impacted teeth, and supernumerary teeth [87].…”
Section: Emerging Trends In Oral Health Sciences and Dentistrymentioning
confidence: 99%
“…However, such images provide a limited 2-dimensional view of the true 3-dimensional (3D) anatomy. With the advent of cone-beam computed tomography (CBCT), accurate 3D images of teeth and their surrounding dentoalveolar structures can be readily obtained[ 8 ], and the technology can accurately provide a minimally invasive approach to acquire detailed diagnostic information[ 9 ].…”
Section: Introductionmentioning
confidence: 99%